И смерть отступала: документальная повесть / Г. Б. Гвоздев - Гвоздев Георгий Борисович (Прапор, 1985)
Экземпляры: КХ (20150311) / Инвентарный номер: 866476 / Цена: 0.30 / Сис.шифр: 9(С)27 / Авт.знак: Г 25 / ГРНТИ: 03 / ББК: 63